Plato's Critique od Democracy and His Concepction of Education for Democracy - Zygmuntowicz, Dorota (Polskie Towarzystwo Filologiczne, 2021)
In the history of the interpretation of Plato’s political thought, the topic of Plato’s criticism of democracy has dominated over his proposal of general and obligatory education (especially literacy) of the demos. Why should we think that the critical aspect is more important than the constructive one? The following paper seeks to demonstrate that these two themes of Plato’s political philosophy are complementary and that awareness of their close interconnection is conducive to our understanding of the reason for, and aims of, Plato’s criticism of democracy as exercised in Athens in the 4th century BC. These arguments are constituted by such main questions as: What does the word demokratia mean to Plato? Why is the quality of laws essential to his description of a “correct regime” (orthe politeia)? Why does a citizen of the law-abiding city of Magnesia in the Laws have to be a reader? Why did Aristotle associate Plato’s name with the utopian ideas presented in the Republic, not with the idea of general educa tion as expressed in the Laws?